INTEGRASI TEKNOLOGI DALAM PENDIDIKAN - Saripudin, Saripudin; Robbani, Muhammad Dzikri Fathur (Prodi Teknologi Pendidikan, 2024)
The integration of technology in education is crucial for preparing the younger generation for the challenges of the Industrial Revolution 4.0. This article explores various technologies that can enhance learning and student skills. Social media, with its popularity and accessibility, offers an interactive platform for collaboration and information exchange between students and teachers, enriching learning experiences through online discussions and resource sharing. Educational simulations and games provide engaging and interactive methods that boost student motivation and help them understand complex concepts through practical experience. AR and VR offer immersive learning experiences, allowing students to explore subjects in a more profound and visual way, thus improving understanding and information retention. AI revolutionizes education by providing personalized learning, analyzing student data to offer tailored recommendations, and automating administrative tasks to enable teachers to focus more on teaching. The article emphasizes that integrating technology in education not only improves learning access and quality but also equips students with relevant future skills. Therefore, collaboration among the government, educators, and the community is essential for effective and sustainable technology implementation in education.Integrasi teknologi dalam pendidikan sangat penting untuk mempersiapkan generasi muda menghadapi tantangan Revolusi Industri 4.0. Artikel ini mengeksplorasi berbagai teknologi yang dapat meningkatkan pembelajaran dan keterampilan siswa. Media sosial, dengan popularitas dan aksesibilitasnya, menawarkan platform interaktif untuk kolaborasi dan pertukaran informasi antara siswa dan guru, memperkaya pengalaman belajar melalui diskusi online dan berbagi sumber daya. Simulasi dan permainan edukatif menyediakan metode yang menarik dan interaktif yang meningkatkan motivasi siswa dan membantu mereka memahami konsep-konsep kompleks melalui pengalaman praktis. AR dan VR menawarkan pengalaman belajar yang imersif, memungkinkan siswa untuk menjelajahi subjek secara lebih mendalam dan visual, sehingga meningkatkan pemahaman dan retensi informasi. AI merevolusi pendidikan dengan menyediakan pembelajaran yang dipersonalisasi, menganalisis data belajar siswa untuk memberikan rekomendasi yang disesuaikan, dan mengotomatisasi tugas administratif sehingga guru dapat lebih fokus pada pengajaran. Artikel ini menekankan bahwa integrasi teknologi dalam pendidikan tidak hanya meningkatkan akses dan kualitas pembelajaran, tetapi juga membekali siswa dengan keterampilan yang relevan untuk masa depan. Oleh karena itu, kolaborasi antara pemerintah, pendidik, dan komunitas sangat penting untuk memastikan implementasi teknologi yang efektif dan berkelanjutan dalam pendidikan